Sheep welfare assessment of meat farms from Spain in different breeds and production systems - Parés, Ricard; Llonch, Pol; Manteca, Xavier; Such, Xavier (Frontiers in Animal Science, 2023)
Sheep production systems are diverse in Europe, and welfare assessment should consider this diversity, including breed type, climatic conditions and time of the year. The aim of this study is to evaluate welfare in one-hundred commercial sheep farms of Spain, therefore in Mediterranean conditions, using a list of twenty-four indicators, which include three for good feeding, five for housing, eleven for health and five for appropriate behaviour. The list includes indicators from the AWIN protocol and other suggested ones.Level of intensification was the main parameter that affected the welfare outcomes of feeding and health, but seasonality and flock size also affected some of the outcomes.Novel indicators included in the list (sternum evaluation, crowding behaviour, subcutaneous abscesses, external parasitism, aggressive behaviours, wool pulling, ear posture and reaction during restraint) were useful to evaluate welfare in Spanish farming conditions, but further studies should be performed to validate them.